Penggunaan Metode Wahdah Dalam Pembelajaran Tahfidzul Quran - Vivi Kautsar Fajriyani; Murniyetti Murniyetti (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to 1) determine the use of the wahdah method in MDTA Darul Quran, 2) determine the implementation of the use of the wahdah method in MDTA Darul Quran, 3) determine the evaluation of the use of the wahdah method in MDTA Darul Quran. The method used by the researcher is a qualitative method with a case study approach. The research was carried out at MDTA Darul Quran, Pantai Cermin District. Data collection was taken from observations, interviews, and documents. The data obtained from the research will be reduced, and conclusions drawn. The data validity technique uses time triangulation, which is re-checking the data with the same technique but at a different time, so as to get valid data. The results of the study show that planning the use of the wahdah method is done well. implementation using the wahdah method is carried out in accordance with the provisions. Evaluation of the use of the method is carried out by depositing the rote memorization to the teacher who teaches.